Reliability Analysis on Repairable System with Dual Input Closed-Loop Feedback Link Considering Shutdown Correlation Based on Goal Oriented Methodology - 伊枭剑 石坚 穆慧娜 张瑶 郭少伟 梁启海 (东华大学学报（英文版）, 2016)
Goal oriented（ GO） methodology is a kind of success oriented system reliability analysis method and has been used widely.The repairable system with dual input closed-loop feedback link（ DICLFL） considering shutdown correlation didn＇t make reliability analysis accurately based on existing GO methodology. So, a reliability analysis method used to deal with DICLFL considering shutdown correlation is provided based on GO methodology.Firstly, a new operator, which is used to describe DICLFL considering shutdown correlation,whose number is 1,is created and named as Type 9C operator. And then,the formulas of type 9C operator are derived based on Markov process theory. Finally,the new method presented in this paper is adopted to conduct the reliability analysis of an electro-hydraulic servo speed control system. The analysis result is compared with those of Monte Carlo simulation and fault tree analysis（ FTA）. The comparison results show that this new reliability analysis method based on GO methodology is feasible and meaningful for reliability analysis of repairable systems with DICLFL considering shutdown correlation.Meantime,it will be useful for more other applications.